MILITANSI YANG RELIGIUS: AKTIVITAS DAN PERANAN TAREKAT BEKTASIYAH DI KERAJAAN OTTOMAN, 1300-1800 - Aldiansyah, Muhammad; Rizal Mahendra, Fahmi (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2024)
This article will explain about the history of the Bektasiyah order, which played an important role in the spiritual axis of the Ottoman warriors from 1300 to 1800. This order was able to give the soldiers a high level of jihad militancy to fight against the sultan's enemies and to expand the empire's territory. Balim Sultan, who was close to Bayezid II, succeeded in institutionalizing the Bektasiyah order into a structured tarekat and emphasized the systematic tarekat tradition. The Bektasiyah Order has its own hierarchy for each follower of the Haci Bektas teachings and each level has a certain role as a dedication to the tarekat. This research was conducted with the aim of studying the Bektasiyah order more deeply related to basic matters such as its role, spiritual teachings, and its relation to the Ottomans. The method used when conducting this research is using historical research methods and library research. In the 13th century AD, the Bektasiyah Order experienced an increase in followers from time to time, even though the teachings taught were antinomian and different from Islamic teachings in general. When entering the modern era, this tarekat experienced difficult times due to the policy of sultan Selim III regarding the elimination of Yanisari soldiers because Yanisari soldiers who were also followers of the Bektasiyah order tended to interfere more in royal political issues and no longer had a solid religious foundation.